115k views
4 votes
Which of the following equation can be used to find the length of LN in the triangle below?

Which of the following equation can be used to find the length of LN in the triangle-example-1
User Lemon
by
5.5k points

1 Answer

3 votes

Given a right angled triangle LMN;

Where MN is the hypothenus;

let LM be the opposite;

then LN is the adjacent.

By the pythagoras theorem;


\begin{gathered} \text{Where h=hypotenus, o=opposite and a=adjacent} \\ h^2=o^2+a^2 \\ o^2=h^2-a^2 \\ a^2=h^2-o^2 \end{gathered}
\begin{gathered} h=33,\text{ o=11 and a=LN} \\ (LN)^2=33^2-11^2 \end{gathered}

CORRECT OPTION: D

User Bailey Miller
by
5.4k points